Epidemiology and Management of Acute Hematogenous Osteomyelitis, Neonatal Osteomyelitis and Spondylodiscitis in a Third Level Paediatric Center - Paola Musso; Sara Parigi; Grazia Bossi; Gian Luigi Marseglia; Luisa Galli; Elena Chiappini (MDPI AG, 2021)
Acute hematogenous osteomyelitis (AHOM) is a rare pathology in pediatric population. The aim of this study is to analyse the epidemiological data and the management, compared to European Society for Paediatric Infectious Disease (ESPID, European Society for Pediatric Infectious Diseases) guidelines 2017 of 216 children with AHOM, divided in three cohorts (neonatal-onset osteomyelitis, those with vertebral involvement and other types of osteomyelitis). We conducted a retrospective single center study, evaluating data from all the children (aged 0-18 years) consecutively admitted to the Meyer Children's Hospital, during a period of ten years (1 January 2010-31 December 2019). Isolation of pathogen was possible in 65 patients and S. aureus was the most frequently involved (43/65 children). Magnetic Resonance Imaging (MRI, magnetic resonance imaging) was performed in 201/216 cases and was compatible with osteomyelitis in 185/201 of these children (92.03%). In the neonatal-onset osteomyelitis group the percentage of diagnostic ultrasound for osteomyelitis was 36.36% significantly higher than the other groups. The median duration of total antibiotic therapy was 37.5 days. In total, 186/199 children recovered without complications. The present study delineates three heterogeneous cohorts of patients. S. aureus is confirmed as the first pathogen for isolation in all three groups analysed. MRI represent a gold standard for diagnosis. Longer duration of antibiotics treatment was performed in neonatal and spondylodiscitis group, compared to the other types of osteomyelitis.